Quasi-Experiment on the Pro-Environmental Attitudes of DKI Jakarta Province Teenagers Influenced by the Documentary Film "Tenggelam dalam Diam" - Alvin, Alvin Iqbal Baihaqi; Sumartias, Suwandi; Erwina, Wina (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
When discussing climate change, one of the effects that is very pronounced is the abrasion and flooding that often occurs in Indonesia, especially in the province of DKI Jakarta, as one of the fastest sinking cities in the world. If this is not controlled, most of the city could be completely submerged by 2050 (Mayuri & Rafki, 2018). In an effort to combat climate change, some research suggests that young people are potentially well placed to trigger ambitious and long-term societal change by adopting sustainable attitudes and behaviours in energy use. (Ouariachi et al., 2017). To determine the increase in pro-environmental attitudes after an experiment using the documentary film "Tenggelam Dalam Diam" for teenagers in DKI Jakarta Province. This study will apply a Nonequivalent group design which is a quasi-experimental research design by comparing two pre-existing groups, where one group receives an intervention (experimental group) and the other group does not receive an intervention (control group) (Creswell, 2014). The results of Asym. Sig. (2-tailed) shows 0.00 which is less than 0.05, it can be stated that the documentary film "Tenggelam Dalam Diam" has an effect on pro-environmental attitudes of DKI Jakarta province teenagers. The results showed that the movie was effective in raising pro-environmental attitudes among teenagers in Jakarta, This research is expected to provide useful information for policy makers and stakeholders, in developing campaign strategies or programs that are more effective in increasing pro-environmnet attitudes and concrete actions towards the environment.